Strategi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Kurikulum Merdeka Belajar pada Sekolah Dasar - Ardeani, Dhika; Farhan, Moh (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
The purpose of writing this article is to find out what the learning strategy for Islamic Religious Education and Characteristics based on Freedom of Learning is in Class 4 at SD N Poncoruso, Semarang Regency, and also to find out the supporting and inhibiting factors that influence the implementation of the learning strategy for Islamic Religious Education and Characteristics based on Freedom of Learning. The research method used is qualitative, using a data collection process in the form of interviews, observation and documentation. The results of the research show that 1) The learning strategy for Islamic Religious Education and Character based on Freedom of Learning for grade 4 students at SD N Poncoruso, Semarang Regency has used learning strategy components which include determining learning objectives, learning activities, resources, materials, as well as tools and evaluation in learning. The learning objectives are based on the development of knowledge, while learning activities include opening activities, core activities, and closing activities. Apart from that, resources, tools and materials are what teachers and students need. For evaluation, use reflection to find dissatisfaction between the two. 2) Supporting and inhibiting factors vary, including the condition of students, availability of infrastructure and teacher readiness.